Poverty, A Risk Factor Overlooked: A Cross-Sectional Cohort Study Comparing Poverty Rate and Cardiovascular Disease Outcomes in the State of Florida. (March 2018) - Al-Turk, Bashar; Harris, Ciel; Nelson, Grant; Smotherman, Carmen; Palacio, Carlos; House, Jeff
The purpose of this study is to examine the relationship between poverty rate and heart disease in our state. A cross-sectional data analysis was performed using figures provided by the Center for Disease Control's Interactive Atlas of Heart Disease and Stroke Tables. Spearman's correlations and simple regressions were used to determine if there was a relationship between poverty and cardiovascular hospitalization rate and cardiovascular death rate. There was a positive monotonic correlation between poverty rate and cardiovascular hospitalization rate (Rho=0.384, P=0.001). There was a positive monotonic correlation between poverty rate and cardiovascular death rate (Rho=0.646, P<0.0001). County poverty rate had a statistically significant positive relationship with cardiovascular hospitalization and cardiovascular mortality in the state of Florida.